The complete chloroplast genome of Verbena officinalis, an herbal species of Verbenaceae family - Yue, Zhiyong (Mitochondrial DNA B Resour, 2021)
Verbena officinalis is one kind of traditional medical herb which has potential for multiple diseases’ treatment. In this study, the complete chloroplast genome sequence of V. officinalis was assembled. Its complete circular chloroplast DNA length was 153,491 bp. The genome was made up of a large single-copy region of 84,518 bp, a small single-copy region of 17,357 bp, and a pair of inverted repeat regions of 25,808 bp. The genome totally encoded 128 genes, containing 83 protein-coding genes, 37 tRNA genes, and eight rRNA genes. Phylogenetic analysis indicates that V. officinalis belongs to the verbenaceae family.